Three unknown early albums of Mark Chagall - Manasherova, Iveta R. (Actual Problems of Theory and History of Art, 2012)
Earlier unknown drawings and poems in Russian of Marc Chagall have begun to come out in foreign publishings since 1984. Th ey came from the archives of Blaise Cendrars. Recently the author got an opportunity to study this material. Three albums with youthful poems of the artist, documentary notes and drawings are presented in this work. Some of them have signatures with dates and indication of place where they were created. All this information lets us to enrich Marc Chagall’s biography at the less known period of his life.
Keywords: Chagall; arts; sketchbook; Vitebsk; Lyozno; cubism; poetry book